Links between vitamin D receptor gene polymorphisms and coronary artery disease: a review of evidence - Maruf-Ur-Rahman, M.; Islam, M. Rafiqul; Begum, Wazeda; Islam, M. Shafiqul; Ara, Hosne (International Journal of Research in Medical Sciences, 2025)
Vitamin D receptor (VDR) serves as a nuclear receptor, playing a significant role in mediating the physiological effects of vitamin D through the regulation of gene expression. Polymorphisms in the VDR gene have the potential impact on receptor activity through modifications in gene transcription, mRNA stability and protein function. Within the extensive array of single-nucleotide polymorphisms (SNPs) identified in the VDR gene, which exceeds 470, four specific variants have captured significant scientific attention: FokI (rs2228570), ApaI (rs7975232), BsmI (rs1544410) and TaqI (rs731236). The examination of these polymorphisms has been conducted within the framework of various diseases, such as malignancies, diabetes mellitus, myocardial infarction and coronary artery disease (CAD). Numerous studies indicate a possible links between these genetic variants and an increased risk of developing CAD; however, discrepancies in findings across various populations and research methodologies persist. This review will thoroughly overview the existing literature regarding the links between VDR polymorphisms and CAD.